Manajemen Pengelolaan Kelas di PAUD Melati III - Sabillah, Anggitha Putri Eka; Darmiyanti, Astuti (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The results of this study show that the management of class management in PAUD MELATI III begins with the placement of facilities and facilities in the room that are suitable for the children's activities to be carried out. The grouping of tables and chairs is tailored to the needs of each child so that they have more room for movement. For the activities of the equipment given security arranged in the room so that it can function when needed by the child. Playing instruments are arranged in such a way that they can train children to be self-reliant, responsible, decision-making, and the habit of rejuvenating equipment that has been used. The walls can be used to adhere to the means that may be used as a source of learning and the results of the child's learning activities, but should not be too much of it to not distract the child during learning. Sunlight tried to get in well so that the class didn't get dark. Classes for early childhood are designed to be fun, with bright and cheerful colors that children like, but not too crowded not to distract children.